2017
DOI: 10.3928/23258160-20171030-05
|View full text |Cite
|
Sign up to set email alerts
|

Single-Spot Yellow Laser Versus Conventional Green Laser on Panretinal Photocoagulation: Patient Pain Scores and Preferences

Abstract: The use of YL-577 as an alternative approach for PRP reduces pain perception and is preferred by patients. [Ophthalmic Surg Lasers Imaging Retina. 2017;48:902-905.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
2
0
2
Order By: Relevance
“…Thermal diffusion of laser energy to the choroid stimulates pain receptors and is related with larger pulse durations and laser wavelengths with deeper penetration to the choroid, while less painful approaches have been described with shorter pulse durations and 532- and 577-nm wavelengths [24-28]. This has been studied in clinical trials mainly using the visual analog scale [29] or a numerical pain scale adapted from the McGill Pain Questionnaire [17].…”
Section: Discussionmentioning
confidence: 99%
“…Thermal diffusion of laser energy to the choroid stimulates pain receptors and is related with larger pulse durations and laser wavelengths with deeper penetration to the choroid, while less painful approaches have been described with shorter pulse durations and 532- and 577-nm wavelengths [24-28]. This has been studied in clinical trials mainly using the visual analog scale [29] or a numerical pain scale adapted from the McGill Pain Questionnaire [17].…”
Section: Discussionmentioning
confidence: 99%
“…While the 577 nm yellow wavelength maintains a negligible uptake by macular xanthophyll and has the highest absorption rate for oxyhemoglobin to melanin absorption ratio, the 810 nm lasers have a very limited scattering in media opacities but present with relatively poor absorption by the retinal pigment epithelium (RPE) and choroid which requires higher power [ 8 ]. Although the yellow wavelength laser seems to be more popular in recent times [ 9 , 10 ] with less power required [ 11 ] and potentially less pain when using the laser for threshold applications [ 12 ], it remains debated which wavelength is optimal for the microsecond pulsing laser application. For example, Chang et al found 810 and 577 nm to be equally effective, but 810 nm had a significantly wider therapeutic range/safety margin [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Por esta razão os lasers mais usados em fototerapia, até o dia presente, são os lasers verde de estado sólido emitindo em 532 nm, isto se deve ao fato de que lasers de estado sólido são no geral de menor custo, boa portabilidade e são facilmente encontrados para compra. Estudos recentes mostraram que a fototerapia laser de retina com o comprimento de onda de 532 nm é mais dolorosa quando comparada aos tratamentos com lasers amarelos [2]. A razão para isto acontecer será melhor explicada na seção sobre fototerapia.…”
Section: Justificativaunclassified
“…A melanina encontrada principalmente no EPR e coroide absorve a maioria da luz que vai do visível ao infravermelho do espectro eletromagnético, e assim é o absorvedor mais eficiente para o processo de fotocoagulação [2,11]. A xantofila tem máxima absorção na luz azul e é encontrada predominantemente na mácula, região onde a absorção da radiação laser é desnecessária, dolorosa e pode causar danos à visão.…”
Section: 133unclassified